Freedom of expression and hate speech regarding the activities of public officials in political debate (Ius Novum, 2024)
Freedom of expression has accompanied mankind for centuries. As societies have developed over the decades, it has evolved and changed. In parallel with it, the brutalisation of language also developed, on the basis of which hate speech developed. Today, it accompanies societies all over the world. However, its most notable impact is in the sphere of the speech of public figures. This is due to the fact that such statements reach a wide audience, which includes both supporters and opponents of such a person. This, in turn, leads to a wide-ranging debate in which individual arguments lose relevance in favour of the repetition of negative slogansand comments with hateful overtones. This statement aims to show the boundary between freedom of expression and hate speech and the consequences that are associated with the use of hate speech by public figures. The article tries to prove the main thesis that the hate speech in the activity of public persons is an unquestionably negative phenomenon, thus it cannot benefit from the protection guaranteed under the freedom of speech. Hence, among the additional theses chosen within the framework of the deliberations, it was assumed that hate speech undermines the dignity not only of individuals but also of the whole society, leads to a lowering of the culture of speech, political and social respectively. Consequently, it violates the authority of public figures and harms the offices they hold by undermining trust in them.
Keywords: freedom of expression, hate speech, public figures